Supervisi Klinik Berbasis 4S (Structure, Skills, Support, and Sustainable) terhadap Penerapan Keselamatan Pasien - Tri Asih Oktariani; Yulastri Arif; Dewi Murni (Universitas Batanghari Jambi, 2020)
Patient safety is a vital matter of a hospital. Reports related to Patient Safety Incident (IKP) continue to increase from 2018 to 2019 in two hospitals namely Abdul Manap Hospital and Raden Mattaher Hospital Jambi. The research aims to analyse the impact of the 4S-based clinical supervision clinic on patient safety implementation of nurse’s practiceat the Jambi Municipal public hospital in 2019. This type of research is quasy experiment with a pre-post approach test design with control group. A sample of implementing nurses amounted to 66 people. Sampling with proportional random sampling. There is a significant influence on the clinical 4S-based clinica lsupervision on the implementation of patient safety by the implementing nurses in the intervention group in the hospital of Raden Mattaher Jambi (0.012) and there is no influence on the application of safety of patients conducted by the implementing nurses in hospital Abdul Manap Jambi City (0.083). Hopefully, the hospital can make the 4S-based clinical supervision to be a routine activity that by making careful planning about the supervision activities performed so that supervision can work to objectives that have been determined.